AN ANALYSIS OF SONGS ON VIDEOS BY EARLY CHILDHOOD IN RETAINING VOCABULARY - Indah, Rosalinda; Fahriany, Fahriany; Haswani, Fahri (UIN Sumatera Utara, 2024)
The core elements of a language are its vocabulary. Early childhood development is a critical time in a person's life that holds great significance for their future. There are problems that young learners face in learning language such as hard to get focused, easy to feel bored, struggle to remember or recall vocabulary items, and still need a stimulus to boost their motivation in the learning process. Learning vocabulary through songs and video making are one of the ways to solve those problems. This current study aims to examine if the songs help young learners in retaining English vocabulary and whether a video making is effective in engaging them in learning vocabulary. This current study used a content analysis design and the samples were 5 students who are 3-7 years old and enrolled English class at RainbowKids BPI. The results showed that songs help early childhood students to retain their English vocabulary. They had memorized all vocabulary on the songs taught to them. They were also able to use pronouns, auxiliary, verb, adjective, and even adverb of degree correctly. Making video is also effective in engaging young learners to improve their English vocabulary and speaking skills.